PERILAKU MENYIMPANG IBU RUMAH TANGGA (STUDI KASUS PERJUDIAN DI KELURAHAN RAMBUNG DALAM KECAMATAN BINJAI SELATAN KOTA BINJAI) - Melly Astari; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Rambung Dalam Urban Village Binjai Selatan District Binjai City. The purpose of this study is to find out what is behind the housewife to do gambling and to find out what the impact of the effects of gambling. The technique of determining the sample by purposive sampling and determine the number of samples as many as 6 people including 5 respondents and 1 key informant. The author uses qualitative descriptive method and data instrument is observation, interview, and documentation. The results of this study indicate that the existence of a gathering of mothers who like to play gambling is really there. In this gambling mothers assume that gambling is a stressor that can alleviate the problems and burdens of the mind they are feeling, where in the game they will forget for a moment about the problems that occur in their lives and get their own satisfaction and can meet his daily hobbies. The factors that lie behind the mothers are gambling is because of family problems and economic problems and several other factors such as environmental factors that make them interested in gambling. Then for the impact of gambling is resulted in a variety of conflicts within the household and the impact felt by children who make children know about gambling. When a person realizes what they are doing is an act deviating from the norms of society they should stop all gambling-related activities that can have an impact on the surrounding environment and can look for other activities to fill in more useful free time such as conducting activities that positive people looking for jobs. Keywords: Deviant Behavior, Housewife, Gambling